A escrita como divã da paixão ou De que modo Agustina Bessa-Luís superou Sigmund Freud - Borges Soares , Mafalda Sofia (Moderna Språk, 2025)
Based on the Freudian character of Agustina’s prose – which doesn’t imply considering Agustina Bessa-Luís’ work as a mere palimpsest but rather including it in certain currents of thought that have continued to appear in her prose at the dawn of the 21st century –, our article will focus on the novel Doidos e amantes, published by Relógio d’Água in 2021. By analysing passages from this still little-studied and untranslated book, we will find out how passion is shaped under Agustina’s aegis, how this passion is experienced – perhaps even suffered – by the protagonist Maria Adelaide and what social consequences this woman is subjected to when she gives in to Eros. We will also see how the Augustinian discourse was able to go further than Freud’s own, since the Portuguese writer didn’t “give up on understanding women”, as the Austrian psychoanalyst did, according to what the Portuguese author states in her Dicionário imperfeito (p. 120). We will therefore aim to complement Freud in the light of Agustina by associating two Freudian works in their French translations with the study of Doidos e amantes: La féminité and Psychologie de la vie amoureuse.